2013
DOI: 10.1038/mi.2012.52
|View full text |Cite|
|
Sign up to set email alerts
|

Systemic vaccination induces clonally diverse SIV-specific CD8+ T-cell populations in systemic and mucosal compartments

Abstract: An HIV-1 vaccine must elicit a clonally diverse virus-specific CD8+ T-cell response to contain mutant virus forms, and these responses must be present in mucosal tissues, which are the site of early HIV-1 replication. We show that systemic delivery of prototype vaccine vectors in rhesus monkeys induced SIV (simian immunodeficiency virus)-specific CD8+ T-cell responses in systemic and mucosal compartments with comparable clonal compositions. Although clonal sharing was maintained between the peripheral blood an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…given time (43). In line with previous studies, we found a degree of clonotype sharing across anatomical compartments (25,26,44), which has likewise been reported in the context of influenza virus infection (45). However, we also identified anatomically unique clonotypes, most frequently in the peripheral blood and the GI tract.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…given time (43). In line with previous studies, we found a degree of clonotype sharing across anatomical compartments (25,26,44), which has likewise been reported in the context of influenza virus infection (45). However, we also identified anatomically unique clonotypes, most frequently in the peripheral blood and the GI tract.…”
Section: Discussionsupporting
confidence: 91%
“…Our data therefore suggest 2 mutually inclusive possibilities. The first is that individual CD8 + T cells are primed in situ and do not traffick extensively between anatomical compartments during chronic infection, implying that systemic vaccination may be required to elicit long-term immunity against HIV/ SIV (26). The second is that public clonotypes are more readily primed during the early stages of infection as a function of prevalence within the naive pool, which can be attributed to convergent recombination (48,49), and subsequently form highly stable tis-sue-resident populations, which are then more likely to be shared across sites of viral replication (27,50).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In an additional study, systemic immunization with SIV Gag, either through a DNA/NYVAC or recombinant BCG/NYVAC prime‐boost strategy elicited potent and durable GI mucosal CD8+ responses. These cells were recruited from the systemic circulating pool early after vaccination and were mostly of the effector memory phenotype . Thus, strong cellular immunity may be achieved at the mucosa through systemic vaccination.…”
Section: Vaccinesmentioning
confidence: 99%
“…However, while the efficacy of intramuscular immunization with IDLV at inducing systemic antigen-specific immune responses after a single immunization is well established, no data are available concerning the mucosal immune responses. Some reports showed that in addition to systemic T cell response, intramuscular immunization was able to induce CD8+ T cell mediated antigen-specific immunity in gut mucosa, an important portal of entry of many infectious pathogens [31], [32].…”
Section: Introductionmentioning
confidence: 99%